DEIXIS IN JACK AND THE BEANSTALK SHORT STORY: CONTEXT MEANING ANALYSIS - El Dina Saifina (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
Deixis is the study of words or phrases that contain the meaning of people, places, and times. Deixis has respective functions based on the classification. The purpose of this study is to find the types of deixis and the meanings of deixis based on the context of the short story. The author used descriptive qualitative methods to analyze the context meaning of deixis in the short story titled Jack and The Beanstalk. The results showed that there were three types of deixis applied in the short story and each of the types has its meaning based on the context. Keywords: Deixis, Short story, Context meaning